APLIKASI CROPWAT 8.0 UNTUK MERENCANAKAN POLA TANAM OPTIMAL DAN MEMAKSIMALKAN HASIL PERTANIAN DI KECAMATAN GUNUNGPATI - Laurentia, Susilawati Cicilia; Arlensietami, Lesty (JURNAL SUMBER DAYA AIR, 2022)
Population growth triggers an increasing agriculture in order to be able to meet food needs. Increasing agricultural yields depends on policies on how to arrange cropping patterns in the reality of water availability and limited field, to provide maximum yields. The Cropwat 8.0 application is part of a computer-based information system (including knowledge-based/knowledge management systems) that is used to support decision making to arrange optimal cropping patterns and maximizing agricultural yields. The purpose of this study was to simulate several alternative cropping patterns in the study area using the Cropwat 8.0 application. From the several alternative cropping patterns simulation, it was determined which could provide maximum agricultural yields. This research was conducted on improving agriculture in Gunung Pati District, using the Cropwat 8.0 application which has 5 input data modules namely climate/ETo, rainfall, crops, soil and cropping patterns as well as 3 calculation data modules namely crop water requirements, irrigation water supply schedules and the number of irrigation water needs of an area in liters per second per Ha. Several alternative simulations are carried out by shifting the planting date or the type of plant and the area of land to find the optimal cropping pattern and provide maximum results. The analysis is generated quickly because every change in cropping pattern, it can immediately know the need for irrigation water in liters/second/hectare to find maximum agricultural yields. The simulation results of several alternatives found the most optimal quickly. Simulations by changing climate data are also generated quickly. This is very helpful for policy makers to determine the right and optimal cropping pattern in a climate change situation that demands speed in responding to maximize agricultural yields so that food availability is sustainable. Keywords: Cropwat 8.0, cropping patterns, optimization of agricultural yields, sustainable food